P-216 The role of a specialist paramedic practitioner in palliative care. (19th November 2022) - Abbas, Syed Qamar; Squires, Jack
Abstract : Background: The paramedic profession was fundamentally based on the provision of out of hospital critical care, intubation and infusion. Since then the profession has grown with a structured career development framework from undergraduate to PhD level education, forming Specialist, Advanced and Consultant Practitioner roles. We report on a paramedic's role and evaluation of their work by colleagues in a hospice setting. Methods: St Clare Hospice employed its first Paramedic and Specialist Paramedic Practitioner undertaking triage and community caseload management for patients living with a palliative diagnosis in West Essex. The roles involve the interrogation of referrals to identify specialist palliative care needs whilst building relationships with patients, their families and carers, from the moment of referral until after their death. Specialist Paramedics work amongst Clinical Nurse Specialists and constantly assess patients for disease progression and the impact of disease on every aspect of their lives. Their role was evaluated by their nurse colleagues working in community team. Analysis: Four colleagues responded to evaluation request. All feedback was positive with themes of new skill, energy among staff, diversity, knowledge and skills, future planning, extended outreach, assessment and communication skills, teamwork, triage and availability. For future development, ideas of rapid response assessments, education, clinics, drop-in sessions and advance care planning support were suggested. Results: Since the appointment of an initial Specialist Paramedic Practitioner, the hospice has grown its AHP workforce to include a second Paramedic. Clear developmental pathways in line with Health Education England and the College of Paramedics Framework have been executed to facilitate learning and professional development within the palliative care setting. Conclusions: The introduction of Paramedics at the hospice has seen a different dynamic to the existing workforce and offered mutual exchange of skills and knowledge, whilst clearly identified career development structures will in turn improve service delivery and patient experience.